FAKTOR YANG MEMPENGARUHI AUDIT DELAY (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2012) - Yanuarizqi, Diazzara Putri (Jurnal Akuntansi AKUNESA, 2013)
The aim of this research is to examine the influence of profitability, internal auditors, company size, and industry sector on the audit delay. This research used 90 companies listed in indonesian stock exchange, selected using purposive sampling method during 2011 until 2012. The hypothesis proposed were tested by multiple linier regression model. From the results it can be concluded that profitability, internal auditors and company size did not significantly and the industry sector variables significantly influence audit delay during the period of this study. Keywords : profitability, internal auditors, company size, and industry sector, and audit delay